2022
DOI: 10.5125/jkaoms.2022.48.5.249
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of tongue squamous cell carcinoma associated with individual surgical margin and pathological features

Abstract: The specific muscular structure of the tongue greatly affects margin shrinkage and tumor invasion, making the optimal surgical margin controversial. This study investigated surgical margin correlated prognosis of TSCC (tongue squamous cell carcinoma) according to margin location and its value, and the histopathologic factors which are suggestive of tumor invasion. And we would like to propose defining of the surgical margin for TSCC via prognosis according to location and margin values. We reviewed 45 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“… 66 previously reported that there was no statistically significant correlation between the T stage and the SD in oral cancer ( P =0.193). A fourth consideration is the association between SD value and tumor aggressiveness 67 . Ota et al .…”
Section: Surgical Margins In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“… 66 previously reported that there was no statistically significant correlation between the T stage and the SD in oral cancer ( P =0.193). A fourth consideration is the association between SD value and tumor aggressiveness 67 . Ota et al .…”
Section: Surgical Margins In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…Additionally, tissue contraction during surgical resection may cause tumor cell clustering and unclear surgical margins 14 . Chemotherapy resistance is also a signi cant factor in postoperative recurrence cases 15 .…”
Section: Introductionmentioning
confidence: 99%